Perilaku Asosiatif Siswa Sekolah Dasar Melalui Pendekatan Bermain Dalam Konteks Pembelajaran PJKO - Aschari Senjahari Rawe (Program Studi Pendidikan Ekonomi, Universitas Flores, 2019)
Social competence is the ability of teachers to relate to the environment of the school community and outside school, teachers are able to get along, communicate, serve the community well, support the creativity of the community, and maintain the emotions and behavior that is not good in the community. With behaviors that can be imitated, the figure of the teacher becomes a parameter of the behavior of the community. This social competence must be the hallmark of the teacher in positioning himself with the community, every move and step of the teacher always gets attention. The change in social relations through physical education activities is the creation of a close sense of unity between learning process actors and the relationship between teacher and student will be better. This happens if the teacher is able to present teaching materials that are appropriate to